Additive Manufacturing Applications in Mission-Critical Operations: A Review - Arup Dey; Olusanmi Adeniran; Monsuru Ramoni; Nita Yodo; Weilong Cong (Journal of Manufacturing and Materials Processing)
Additive manufacturing (AM) is used to fabricate complex components from a wide variety of materials in an additive manner. AM brings several benefits, such as reduced lead times, on-demand production, creation of complex customized designs without tooling requirements, and remote design sharing. However, the use of AM for critical components is limited in large missions due to quality and reliability concerns, as is the case with many manufacturing technologies. Enhancing the acceptance of AM-built parts for mission-critical components can be achieved by producing highly reliable parts, establishing robust quality standards, and continually improving part properties. This review article comprehensively explores the diverse potential applications of AM within mission-critical operations, along with its potential benefits and the advancements needed for broader acceptance. Delving into the intersection of AM technologies and mission-critical requirements, the paper examines possible challenges of utilizing AM techniques in mission-critical components. Through an in-depth analysis of relevant studies, the article aims to provide a nuanced understanding of the current state of AM applications in mission-critical operations, offering insights into the potential benefits, limitations, and future directions for this innovative technology. The findings presented in this review are valuable for researchers, academics, and industry professionals working to advance AM technologies for mission-critical applications.